Economic Burden of Otitis Media Globally and an Overview of the Current Scenario to Alleviate the Disease Burden: A Systematic Review - Bhatia, Ragini; Chauhan, Anil; Rana, Monika; Kaur, Kulbir; Pradhan, Pranita; Singh, Meenu (International Archives of Otorhinolaryngology, 2024)
Introduction The prevalence of otitis media (OM) is substantial all over the world. Epidemiological data related to the economic burden of OM globally is minimal. The present systematic review was undertaken to estimate the economic burden of this disease in various parts of the world.Objectives An extensive literature search was done using PRISMA guidelines to identify relevant studies that estimated the economic burden of OM in monetary terms. The databases searched were PubMed Central, Ovid, and Embase. The cost estimation was done for one specific year and then compared considering the inflation rate.Data Synthesis The literature search led to the inclusion of 10 studies. The studies evaluated direct and indirect costs in monetary terms. Direct costs (health system and patient perspective) ranged from USD (United States Dollar) 122.64 (Netherlands) to USD 633.6 (USA) per episode of OM. Looking at only the patient perspective, the costs ranged from USD 19.32 (Oman) to USD 80.5 (Saudi Arabia). The total costs (direct and indirect) ranged from USD 232.7 to USD 977 (UK) per episode of OM. The economic burden per year was highest in the USA (USD 5 billion). The incidence of OM episodes was found more in children < 5 years old. Introduction of pneumococcal conjugate vaccines decreased the incidence in children and now the prevalence in adults is of concern.Conclusion The economic burden of OM is relatively high globally and addressing this public health burden is important. Approaches for the prevention, diagnosis, and treatment should be undertaken by the health system to alleviate this disease burden.
Keywords: otitis media; direct costs; indirect costs; economic burden